การผลิตปุ๋ยอินทรีย์ชีวภาพอัดเม็ดสูตรผสมเพื่อการผลิตข้าวต้นทุนต่ำ - Intanon, Pumisak; Sawamichai, Ratana; KluayNgern, Boonsong (Asian Health, Science and Technology Reports, 2012)
This study aimed to reduce the cost of rice production and to increase production yield. The experiment was undertaken at Village No. 4, Tambon Thapho, Muang District, Phitsanuloke during April- August 2011. The RCBD experiment design with 6 treatments and 3 replications for each treatment was employed. The total treatments were 18. The treatments consisted of the following: T0 control (no fertilizer), T1 (pellet organic fertilizer from farm manure), T2 (granular organic fertilizer made from bio liquid and rock minerals), T3 (compound pellet organic fertilizer from several organic materials), T4 (46-0-0 chemical fertilizer) and T5 (16-20-0 chemical fertilizer). For each type of fertilizer, 50 kg per Rai (1,600 m 2 ) was utilized (applied). The Kokho No. 41 rice variety was used in the experiment. The data on micro climate at the research site, pre- and post- experiment soil properties, plant vegetative growths, yield and yield components, income and rice production cost per area or 1 square meter) were collected. The statistics used to test the means of multiple groups were ANOVA and Duncan’s Multiple Range Test (DMRT), with the confidence level of 95%. The findings revealed that the organic fertilizer used in T3 was shown to have the highest content of both major elements (N-PK) and minor elements (Ca-Mg-S). Vegetative growths such as stem height and number of leaves were found highest in T4, followed by T5, T3, T2, T1 and T0, respectively. The number of stems per plant was found highest in T3 (compound pellet organic fertilizer from several organic materials) This was because this type of fertilizer contains more properties for improving soil physically, chemically and biologically than any other type of fertilizer. In the analysis of yields and yield component such as the number of seeds per ear and the number of seed stunted per ear, it was found that T0 (no fertilizer) and T4 (46-0-0) were found to have the highest number of seeds, but they were not good for the increase in rice production. The number of ear per one square meter, ear weight and the total weight of 1,000 seeds were found highest in T3, with the average yield of 864.4 kg/Rai (1,600 m 2 ), followed by T2 (with 817.7 kg), T5 (with 736.5 kg), T1 (with 679.1 kg/Rai) and T0 (with 625.0 kg/rai), respectively. In terms of income generation per Rai (1,600 m 2 ), T3 was found to generate the highest income (12,101.6 baht), followed by T2 (11,447.8 baht), T5 (10,311.0 baht), T1 (9,507.4 baht), T4 (9079.0 baht) and T0 (8750.0 baht), respectively. The cost and profit analysis found that T3 yielded the highest net profit of 7,141.6 baht/Rai, followed by T2 (with 6,187.78 baht/Rai), T5 (with 4471.4 baht/Rai), T1 (with 4,147.4 baht/Rai), T0 (with 3,890 baht/Rai) and T4 (with 3,299.0 baht/Rai), respectively. From the findings, it can be concluded that T3 is the best method for rice production because of its highest net profit highest yield per Rai, and lowest cost for production of 1 kilogram of rice.